Reverse Faber-Krahn inequality for the p-Laplacian in hyperbolic space - Ghosh M.; Verma S. (My University, 2025)
In this paper, we study the shape optimization problem for the first eigenvalue of the p-Laplace operator with the mixed Neumann-Dirichlet boundary conditions on multiply-connected domains in hyperbolic space. Precisely, we establish that among all multiply-connected domains of a given volume and prescribed (n−1)-th quermassintegral of the convex Dirichlet boundary (inner boundary), the concentric annular region produces the largest first eigenvalue. We also derive Nagy's type inequality for outer parallel sets of a convex domain in the hyperbolic space. © 2023 Elsevier Inc.